EVALUATION OF EDUCATION AND TRAINING PROGRAM AT MEDAN RELIGIOUS TRAINING CENTER - Rahmadi Ali; Rofiqoh Hasan Harahap (JURNAL AL-TANZIM, 2021)
This study aims to analyze and evaluate the context, input, process, and product of a substantive technical training program for preparing lesson plans for Madrasah Ibtidaiyah teachers. The study used a qualitative approach with the CIPP evaluation model (context, input, process, and product). The results showed that; first, the context dimension states that the implementation of education and training is by the legal basis for working; second, the input dimension includes the availability of reliable resources, adequate facilities, and infrastructure and financing borne by the government, so that its implementation can be carried out properly; third, the dimension of the process which includes the implementation of programs that are by the predetermined plans and designs; fourth, the product dimension where the teacher already understands the specified competencies.